2019
DOI: 10.1186/s12879-019-3843-4
|View full text |Cite
|
Sign up to set email alerts
|

High expression of IDO1 and TGF-β1 during recurrence and post infection clearance with Chlamydia trachomatis, are independent of host IFN-γ response

Abstract: Background Chlamydia trachomatis infections in women continue to be a major public health concern due to their high prevalence and consequent reproductive morbidities. While antibiotics are usually efficient to clear the Chlamydia , repeat infections are common and may contribute to pathological outcomes. Interferon-gamma (IFN-γ)-mediated immunity has been suggested to be protective against reinfection, and represent an important anti-chlamydial agent, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…We investigated the hypothesis that TGF-␤ signaling cooperates with the EGFR signaling pathway for the cytoskeletal reorganization that supports optimal chlamydial inclusion development and for stable EMT induction. Figure 1a confirms previous reports (40,41) that upregulated TGF-␤ expression is induced during chlamydial infection (P Ͼ 0.0001). The induction occurred within 6 h of infection of epithelial cells.…”
Section: Upregulation Of Tgf-␤ Expression and Activation Of The Signasupporting
confidence: 90%
See 2 more Smart Citations
“…We investigated the hypothesis that TGF-␤ signaling cooperates with the EGFR signaling pathway for the cytoskeletal reorganization that supports optimal chlamydial inclusion development and for stable EMT induction. Figure 1a confirms previous reports (40,41) that upregulated TGF-␤ expression is induced during chlamydial infection (P Ͼ 0.0001). The induction occurred within 6 h of infection of epithelial cells.…”
Section: Upregulation Of Tgf-␤ Expression and Activation Of The Signasupporting
confidence: 90%
“…It has been established that Chlamydia binds EGFR and activates the EGFR signaling pathway, which plays a crucial role in host cell invasion and cytoskeletal reorganization for a productive infection with optimal inclusion development (8,9,(32)(33)(34)(35)(36)42). The EGFR and TGF-␤ signaling pathways also often synergize to mediate cytoskeletal reorganization, leading to stable EMT induction (20,43), and Chlamydia induces EMT (6) as well as upregulates TGF-␤ expression in humans and animals (40,41). However, the involvement of TGF-␤ in chlamydial inclusion development and chlamydia-induced EMT is unknown.…”
Section: Upregulation Of Tgf-␤ Expression and Activation Of The Signamentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, the levels of IFNg measured were significantly below those needed to clear Ct infections in in vitro models (Shemer and Sarov, 1985;Arno et al, 1990), suggesting additional factors may be at work in vivo in women. In vitro studies by Ziklo et al have shown that Ct can induce IDO1 expression in the absence of IFNg, further suggesting alternative regulatory pathways for IDO-1-induced tryptophan degradation (Ziklo et al, 2019). Additionally, Jordan et al found decreased IFNg concentrations in those that cleared Ct compared to those with a persistent infection, which could reflect the decreased production of IFNg once Ct is cleared (Jordan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase gene (GAPDH) was used as housekeeping gene. RANTES and TGF-β1 expression were measuring according to Ziklo et al protocols [ 13 ]; first mRNA was reverse-transcribed using radom primers and SuperScript® Reverse Transcriptase Kit (Invitrogen, Life Technologies). cDNA synthesized was use as template in PCR reaction using QuantiFastTMSYBR® Green PCR Kit (QIAGEN, Germany).…”
Section: Methodsmentioning
confidence: 99%